Theoretical Grounds of Educational Managers’ Training to the Social and Pedagogical Projects Management - Barban, Marianna (Pedagogical Discourse, 2012)
There are theoretical grounds of educational managers’ training to the social and pedagogical projects management in article. Author defines and considers general pedagogic, andragogic, acmeologic principles and action, competence based, clustered, acme-synergetic approaches, which provide successful this training. Also, pedagogical conditions that contribute the effectiveness of training are presented.